Synthesis and Antimicrobial Activity of 1,3-Thiazines. - B. RAGHUWANSHI, PRAVIN; DOSHI, A.G. (Asian Journal of Chemistry, 2010)
Nitrochalcones react with thiourea or diphenylthiourea in alkaline medium to give 1,3-thiazines in 3 h and yields are found to be 50–60%. The same reaction was carried out in DMSO medium in presence of sodium methoxide and it was interesting to find that the reaction takes place in 15 min and gives better yield. 1,3-Thiazines possess antibacterial and antifungal properties when assayed against the test organisms.